2018
DOI: 10.1159/000493814
|View full text |Cite|
|
Sign up to set email alerts
|

Propofol Inhibits Proliferation, Migration, Invasion and Promotes Apoptosis Through Down-Regulating miR-374a in Hepatocarcinoma Cell Lines

Abstract: Background: Propofol is a commonly used anaesthetic with controversial effects on cancer cells. We aimed to explore the functional roles of propofol in hepatocellular carcinoma (HCC) cells as well as the underlying mechanisms. Methods: HepG2 and SMMC-7721 cells were used in this study. Firstly, the effects of propofol on cell viability, migration, invasion, apoptosis, and involved proteins were assessed by Cell Counting Kit-8 assay, Transwell assay, flow cytometry assay and Western blot analysis, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Zhang et al (31) demonstrated that propofol promoted the apoptosis of cervical cancer cells by regulating the mTor signaling pathway. liu et al (32) also concluded that propofol suppressed the growth, migration and invasion of hepatocellular carcinoma cells by downregulating miRNA expression. Propofol enhanced the apoptotic effect of ddP on cervical cancer, which subsequently increased the sensitivity of cancer cells to the chemotherapeutic effect of ddP (33), whereas another study reported that propofol altered the resistance of prostate cancer cells to docetaxel by inducing hypoxia (34).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (31) demonstrated that propofol promoted the apoptosis of cervical cancer cells by regulating the mTor signaling pathway. liu et al (32) also concluded that propofol suppressed the growth, migration and invasion of hepatocellular carcinoma cells by downregulating miRNA expression. Propofol enhanced the apoptotic effect of ddP on cervical cancer, which subsequently increased the sensitivity of cancer cells to the chemotherapeutic effect of ddP (33), whereas another study reported that propofol altered the resistance of prostate cancer cells to docetaxel by inducing hypoxia (34).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol also showed an inhibitory role in the adhesion of hepatocellular carcinoma cells via enhancing the expression of miR‐199a . Cell apoptosis could be induced while cell viability could be repressed by propofol through its regulations on several miRNAs including miR‐374a, miR‐24, miR‐486 and miR‐451 in different types of cancer cells . In fact, these functions of propofol were observed in numerous cancers.…”
Section: Discussionmentioning
confidence: 99%
“…8 Cell apoptosis could be induced while cell viability could be repressed by propofol through its regulations on several miRNAs including miR-374a, miR-24, miR-486 and miR-451 in different types of cancer cells. [22][23][24][25] In fact, these functions of propofol were observed in numerous cancers. Recently, pancreatic cancer malignancy was found to be suppressed by propofol via down-regulating vascular endothelial growth factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…26 Laboratory data provide support for the effect of propofol on HCC cancer growth and survival through several different pathways. 27e29 Using human HCC cell lines, Liu and colleagues 27 reported that propofol inhibited the proliferation, migration, and invasion of HCC cells via downregulation of miR-374a. Zhang and colleagues 28 reported that propofol decreased HCC cell invasion, partly through downregulation of matrix metalloproteinase 9 (MMP-9) expression by miR-199a.…”
Section: Discussionmentioning
confidence: 99%